Mortality among persons experiencing musculoskeletal pain: a prospective study among Danish men and women - Holmberg, Teresa (BMC Musculoskelet Disord, 2020)
BACKGROUND: Musculoskeletal (MSK) pain affects many people worldwide and has a great impact on general health and quality of life. However, the relationship between MSK pain and mortality is not clear. This study aimed to investigate all-cause and cause-specific mortality in relation to self-reported MSK pain within the last 14 days, including spread of pain and pain intensity. METHODS: This prospective cohort study included a representative cohort of 4806 men and women aged 16+ years, who participated in a Danish MSK survey 1990–1991. The survey comprised questions on MSK pain, including spread of pain and pain intensity. These data were linked with the Danish Register of Causes of Death to obtain information on cause of death. Mean follow-up was 19.1 years. Cox regression analyses were performed with adjustment for potential confounders. RESULTS: In the study population (mean age 44.5 years; 47.9% men), 41.0% had experienced MSK pain within the last 14 days and 1372 persons died during follow-up. For both sexes, increased all-cause mortality with higher spread and intensity of MSK pain was observed; a high risk was observed especially for men with strong pain (HR = 1.66; 95% CI:1.09–2.53) and women with widespread pain (HR = 1.49; 95% CI:1.16–1.92). MSK pain within last 14 days yielded c-statistics of 0.544 and 0.887 with age added. Moreover, persons with strong MSK pain had an increased cardiovascular mortality, persons with moderate pain and pain in two areas had an increased risk of cancer mortality, and persons with widespread pain had an increased risk of respiratory mortality. CONCLUSIONS: Overall, persons experiencing MSK pain had a higher risk of mortality. The increased mortality was not accounted for by potential confounders. However, when evaluating these results, it is important to take the possibility of unmeasured confounders into account as we had no information on e.g. BMI etc. SIGNIFICANCE: The present study provides new insights into the long-term consequences of MSK pain. However, the discriminatory accuracy of MSK pain was low, which indicates that this information cannot stand alone when predicting mortality risk.